2018
DOI: 10.1152/japplphysiol.00768.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between androgen and Wnt signaling potentially contributes to age-related skeletal muscle atrophy in rats

Abstract: We sought to determine whether age-related gastrocnemius muscle mass loss was associated with parallel decrements in androgen receptor (AR) or select Wnt signaling markers. To test this hypothesis, serum-free and total testosterone (TEST) and gastrocnemius AR and Wnt signaling markers were analyzed in male Fischer 344 rats that were 3, 6, 12, 18, and 24 mo (mo) old ( n = 9 per group). Free and total TEST was greatest in 6 mo rats, and AR protein and Wnt5 protein levels linearly declined with aging. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
(47 reference statements)
3
12
0
Order By: Relevance
“…The presence of T increases AR-β-catenin interaction and transcriptional capacity. Positive correlations were shown between AR protein content and Wnt5 expression and muscle mass and Wnt5 expression in rats (44). Testosterone treatment increased Wnt5 protein expression and muscle size in a dosedependent manner (44).…”
Section: Androgen Signaling Pathwaysmentioning
confidence: 91%
See 1 more Smart Citation
“…The presence of T increases AR-β-catenin interaction and transcriptional capacity. Positive correlations were shown between AR protein content and Wnt5 expression and muscle mass and Wnt5 expression in rats (44). Testosterone treatment increased Wnt5 protein expression and muscle size in a dosedependent manner (44).…”
Section: Androgen Signaling Pathwaysmentioning
confidence: 91%
“…Positive correlations were shown between AR protein content and Wnt5 expression and muscle mass and Wnt5 expression in rats (44). Testosterone treatment increased Wnt5 protein expression and muscle size in a dosedependent manner (44). Spillane et al (45) reported significant up-regulation of VL muscle β-catenin following upper and lower body RT at 3 and 24 h PE and increased AR-DNA binding capacity and suggested the increased binding capacity was linked to greater β-catenin pathway signaling.…”
Section: Androgen Signaling Pathwaysmentioning
confidence: 99%
“…Cell culture methods were performed similar to other studies published by our laboratory (16,17). Brie y, C2C12 myoblasts (passage 6; American Type Culture Collection, Manassas, VA, USA), were seeded in growth medium (DMEM, 10% FBS, 1% penicillin/streptomycin, and 0.1% gentamycin) on six-well plates at a seeding density of 3 x10 5 under standard culture conditions (37°C in a 5% CO 2 atmosphere).…”
Section: Cell Culturementioning
confidence: 99%
“…MAR1 also affects myogenesis by enhancing Wnt5a function [54]. Wnt5a may contribute to age-related skeletal muscle atrophy in rats [55]. These studies suggest that MAR1 may be involved in the Wnt5a-regulated muscular atrophy pathway.…”
Section: Lncrnas In Skeletal Muscle Diseasementioning
confidence: 99%